2015
DOI: 10.4161/2162402x.2014.984547
|View full text |Cite
|
Sign up to set email alerts
|

The correlations between IL-17 vs. Th17 cells and cancer patient survival: a systematic review

Abstract: Both IL-17 and Th17 cells have been ascribed tumor promoting as well as tumor suppressing functions. We reviewed the literature on correlations between IL-17 versus Th17 cells and survival in human cancer, following the PRISMA guidelines. Serum, formalin-fixed, paraffin-embedded (FFPE) tissue and peripheral blood samples were most frequently studied. High IL-17 quantities were correlated with poor prognosis, whereas high Th17 cell frequencies were correlated with improved prognosis. Since Th17 cells are a subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
78
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 79 publications
5
78
0
2
Order By: Relevance
“…Moreover, knocking down BATF3 in Th2 cells dramatically decreased expression of IL4 and IL10 cytokines (41, 42). This is an intriguing biological connection as both the overexpression of IL10 and elevated levels of Th17 cells in peripheral blood were correlated with improved cancer patient survival in previous studies (43, 44). These findings therefore align with our observations that minor T allele carriers of germline eQTL rs6695772, associated with worse OS, express low levels of BATF3 which may in turn down-regulate IL4 and IL10 .…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, knocking down BATF3 in Th2 cells dramatically decreased expression of IL4 and IL10 cytokines (41, 42). This is an intriguing biological connection as both the overexpression of IL10 and elevated levels of Th17 cells in peripheral blood were correlated with improved cancer patient survival in previous studies (43, 44). These findings therefore align with our observations that minor T allele carriers of germline eQTL rs6695772, associated with worse OS, express low levels of BATF3 which may in turn down-regulate IL4 and IL10 .…”
Section: Discussionmentioning
confidence: 67%
“…Altogether our data reveal a positive contribution of Th17 cells to beneficial antitumour immune responses developing in CRC and underline their pleiotropic function resulting from the production of a broad spectrum of cytokines and chemokines beyond IL- 17. This may, at least partially, explain the discrepancies between results obtained from studies evaluating the effects of IL-17 or IL-17 signalling only and those examining functions of the whole Th17 cell subset. [47][48][49][50] Our findings have important clinical implications. Indeed, the positive contribution of Th17 to anti-tumour immune responses should not be disregarded when developing new IL-17/Th17 targeted treatments in CRC, possibly resulting in impaired tumour infiltration by beneficial effector cells.…”
Section: Discussionmentioning
confidence: 68%
“…Although our results were limited to peripheral circulating samples, an MDSC-IL-17-VEGF axis seems to be present in patients with gastric and colorectal cancers, and, more importantly, this axis seems to be closely related to cancerrelated systemic infl ammation, immune suppression, and nutritional impairment. With regard to prognosis, expressions of VEGF and IL-17 are reported to be independent significant prognostic factors in patients with various cancers 20,21,27,28) . In the present study, we also confi rmed that worse prognoses was signifi cantly observed in both stage III and IV gastric and colorectal cancers for patients exhibiting high production of IL-17 or high serum levels of VEGF than those having low levels of IL-17 or VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that IL-17 induces VEGF-A expression via signal transducer and activator of transcription (STAT)-3 signaling mechanisms 27,28) . MDSCs have been reported to express receptors for VEGF-A and be activated by VEGF-A, and distribution of Treg cell may also increase through MDSC-associated mechanisms 25,26) .…”
Section: Discussionmentioning
confidence: 99%